2022
DOI: 10.3390/nu14194095
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hyperuricemia and Its Correlates among Adults in China: Results from CNHS 2015–2017

Abstract: This study aimed to investigate the prevalence of hyperuricemia (HUA) and associated risk factors in Chinese adults aged 18 to 59 years. All the data were collected from the China Nutrition and Health Surveillance during the period 2015–2017, which adopted a stratified, multistage, random sampling method on a national scale. A total of 52,627 participants aged 18 years or older were included in this study. The definition of hyperuricemia was 420 μmol/L for male and 360 μmol/L for female. The Rao–Scott chi-squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 53 publications
1
27
0
1
Order By: Relevance
“…HUA and HTN share several common risk factors, including age, obesity, TC and TG [30][31][32][33]. This overlap suggests that individuals with HTN may have a higher propensity to develop HUA.…”
Section: Discussionmentioning
confidence: 99%
“…HUA and HTN share several common risk factors, including age, obesity, TC and TG [30][31][32][33]. This overlap suggests that individuals with HTN may have a higher propensity to develop HUA.…”
Section: Discussionmentioning
confidence: 99%
“…First, harmful drinking increases the production of uric acid and inhibits the excretion of uric acid. 39 , 44 Secondly, harmful alcohol use causes acute liver damage, which affects the production of uric acid metabolic enzymes and uric acid transporters. One study indicated xanthine oxidase inhibition could reduce uric acid production.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that, in patients with CKD5, gender, BUN, P, and TG were independent risk factors for elevated serum uric acid levels. Previous epidemiological and mechanistic studies have veri ed that a number of variables, including genetics, gender, age, diet, diabetes, and hypertension, have an impact on SUA levels 37 . According to a metaanalysis, male patients with hyperuricemia in mainland China had an average serum uric acid level that was higher than that of female patients, and the gender prevalence was also signi cantly different, with male patients having a prevalence of 19.4% and female patients having a prevalence of 7.9% 38 .…”
Section: Discussionmentioning
confidence: 99%